Asociación entre poros y fibras en la estructura anatómica de ramas de Guattería elata, Puerto Almendra, Loreto, Perú - 2021 - Puga de la Cruz, Carlos (2022)
The research was developed in the Laboratory of Anatomy and Wood Technology. The samples were obtained in the Arboretum "El Huayo" of the FCF - UNAP, San Juan Bautista district, Maynas province, Loreto region. The objective was to determine the degree of association between pores and fibers in the anatomical structure of the branch of G. elata. The best association was obtained considering the pore diameter as an independent variable, the best fitting allometric model was the quadratic Y = - 17.065 + (28.813 x t) + (- 0.116 x t2) (r = 0.355; r2 = 0.126), indicating a regular degree of association.